Foregrounding Affectivity in the Pathways to Extremism - Shaheed, Saad; Haq, Hina (Advances in Social Sciences Research Journal, 2024)
Literature increasingly indicates that affectivity plays a major role in violent extremism. Nevertheless, much of the work on affectivity in the context of violent extremism has so far remained a fragmented background issue. The purpose of this paper is to bring affect to the foreground through philosophical accounts of situated affectivity, while remaining compatible with contributions on emotions and affect from different disciplines in the context of extremism. The situated account explains how environmental structures affect individual affectivity and vice versa. With the help of this framework, we are able to analyze an individual’s affective dynamics simultaneously with multiple elements. By using different analytical vantage points, we can examine how the affectivity of individuals is shaped and regulated by other individuals, materials, spaces, discourses, and behaviors in extremist settings. The approach provides a broader and richer perspective on the complexities and dynamics of affect in extremism. Affect-centric counter- and preventive policies relating to violent extremism can benefit from this approach.